The Effect of Work Discipline on Employee Performance Apron Movement Control (AMC) at Umbu Mehang Kunda Waingapu Airport, East Sumba - Wiligis Aditya Harumbaha; Septiyani Putri Astutik (CV. Rayyan Dwi Bharata, 2023)
Umbu Mehang Kunda Airport is one of the Airport Service Unit (UPBU) airports located in the city of Waingapu, East Sumba district, East Nusa Tenggara Province, Indonesia. The purpose of this study is to find out whether work discipline affects the performance of Apron Movement Control (AMC) employees at Umbu Mehang Kunda Waingapu Airport, and how much work discipline affects the performance of Apron Movement Control (AMC) employees at Umbu Mehang Kunda Waingapu Airport, Sumba. East. This research uses quantitative methods in an effort to test the hypotheses that have been prepared. To find out the effect of work discipline on the performance of Apron Movement Control (AMC) employees at Umbu Mehang Kunda Waingapu Airport, a questionnaire was carried out to 40 respondents consisting of officers from the Ground Handling, Customer Service, Pkp-Pk, and Atc units who coordinated with Apron Movement Control (AMC) officers who are the object of this research, then the results of the respondents' answers are convected using a Likert scale and calculated using the SPSS program. Based on the T test results of this study that there is an influence of Work Discipline on Employee Performance Apron Movement Control (AMC) at Umbu Mehang Kunda Waingapu Airport, East Sumba. Judging from the results of the tcount calculation of 6.323 above compared to ttable which is 2.024 at a significant level of 5%, so t count t table. Based on the results of these calculations, it was also obtained that the coefficient of determination (R2) was 0.513 that there was an effect of the Work Discipline variable on the Employee Performance variable of 51.3% and the remaining 48.7% was influenced by other factors which in this case were not examined.